HARNESSING INDIGENOUS FARMING KNOWLEDGE TO ENHANCE FOOD SECURITY AND LAND CONSERVATION IN MUBI NORTH LGA, ADAMAWA STATE, NIGERIA - Garandi, Danjuma Ijudigal; Bashir, Abbas; Dasin, Mohammed Saadu (FUDMA JOURNAL OF SCIENCES, 2025)
The study investigates the role of indigenous farming knowledge in conservation practices and sustainable food security in Mubi North LGA, Adamawa State. The research seeks to achieve through the following objectives, to assessed the extent to which indigenous farming practices contribute to conservation farming and examining their impact on food security. and to investigate the contributions of indigenous farming knowledge toward achieving sustainable food security in Mubi North LGA, Adamawa State.  Utilizing a mixed-methods approach, both primary and secondary data sourced were used, data were collected through structured questionnaires and interviews of randomly selected 349 farmers and 15 agricultural officials in Mubi North LGA of Adamawa State sample size were determined using Cochran’s formula, Liker scale was employed for measuring respondents’ perception and Descriptive statistics were used to summarize data, while hypothesis was tested using t-test analysis.  Findings reveal a high awareness of indigenous techniques, particularly in soil preservation and crop diversity. A mean score of 4.47 highlights the effectiveness of traditional methods in restoring soil fertility, while a grand mean of 3.32 indicates farmers recognize the benefits of these practices for food safety and affordability. Notably, a t-test analysis indicates significant differences in perceptions between adopters and non-adopters of indigenous practices, emphasizing the positive effects on land conservation among those who adopt. The study concludes that indigenous farming knowledge plays a crucial role in enhancing agricultural sustainability and food security in the region. Recommendations include enhancing education and training for farmers, innovating traditional storage methods, and strengthening support networks...
Keywords: Indigenous Farming Knowledge; Conservation Practices; Sustainable Food Security; Environmental Challenges